THE EFFECT OF SERVICE QUALITY AND CUSTOMER VALUE ON REPURCHASES THROUGH CUSTOMER SATISFACTION OF INDONESIAN SHARIA MOBILE BANKING USERS IN SEMARANG - Ulumiah Miftachul; Naili Farida; Listyorini Sari (Jurnal Ekonomi, 2023)
The industrial revolution 4.0 in Indonesia has an impact on the financial services sector in order to adapt to the changing order in financial services. The main change is the change in digital strategy. One of the digital strategies owned by Islamic banking is mobile banking services. Although Bank Syariah Indonesia is the result of marger from BRI Syariah, BNI Syariah and Mandiri Syariah, mobile banking users are still far from the expected target, Islamic banking continues to increase socialization and literacy related to mobile banking at Bank Syariah Indonesia. Bank Syariah Indonesia's desire for mobile banking user customers is to make repurchases, when the repurchase of these services is carried out, it shows that customers have begun to need mobile banking services. Customers make repurchases influenced by customer satisfaction in using the mobile banking application. Customers feel satisfaction, one of which comes from the quality of services provided by Bank Syariah Indonesia, when customers have used it, customers can assess Bank Syariah Indonesia mobile banking services. The population in this study were users of mobile banking services in Semarang. The sample was 100 people and the sampling technique was purposive sampling and analysis techniques using Structural Equation Modeling (SEM) Partial Least Square or PLS. This study aims to determine the influence of service quality and customer value on repurchases through customer skills of Bank Syariah Indonesia mobile banking users, this study uses 3 hypotheses, namely Hypothesis 1 explaining the positive and significant influence of service quality on customer satisfaction, Hypothesis 2 explains the positive and significant influence of ulanh purchases on customer satisfaction, and Hypothesis 3 explains the positive and significant effect of customer satisfaction on repurchases.